Ībistīmūlūjiyya Al-Manāhij al-Dirāsiyyah fī Pesantren: Ru’yah Tajdīdiyyah li Ta‘limi al-Lugah al-‘Arabiyyah / Epistemology Curriculum in Pesantren Indonesia: A New Vision for Arabic Learning - Muhajir Muhajir (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
This article aims to know the development of Arabic language education and the formation of the new epistemological curriculum. This goal appears to treat after the problems facing institutes in designing the curriculum in teaching the language of the Qur'an. After reviewing the data, analyzing it, and discussing it with the appropriate theories, the researcher concluded the following: The first was teaching the Arabic language in the Pesantren using the grammar method and the efficiency of reading religious texts. The second type, which focuses on the Arabic language as a communication tool, is widely used in institutes: modern Islamic education and many modern Islamic educational institutions. The third type of Arabic language education has been used in formal education (public schools and religious schools). It continues to be supplemented, whether in terms of curricula, educational goals, materials, method, or teaching strategies as methods used. Teaching the Arabic language needs to develop a new curriculum that focuses on teaching competencies, namely specific and specific competencies, language competencies, and communicative competencies. These competencies are linked to each other, especially in linguistic and communicative competencies. Keywords: Curriculum, Arabic Learning, Pesantren, Competencies. ملخص الأهداف المنشودة لهذه المقالة هي معرفة تطوير في تعليم اللغة العربية وتكوين المنهج الابستيمولوجي الجديد فيه. يظهر هذا الهدف لعلاج بعد المشاكل التي تواجه المعاهد في تصميم المنهج الدراسي فى تعليم لغة القرأن. بعد مراجعة البيانات وتحليلها ومناقشتها بالنظريات المناسبة استخلص الباحث فيما يلي: الأول تم تعليم اللغة العربية في الـمعاهد الإسلامية السلفية (باسانترين) بإستخدام طريقة القواعد وكفاءة قرأة النصوص الدينية. وأما النوع الثاني الذي يركز على أن اللغة العربية أداة الاتصال فيستخدم على نطاق واسعفي الـمعاهد الإسلامية الـعصرية، وعدد كبير منالـمؤسسات التعليمية الإسلامية الحديثة. وأما النوع الثالثلتعليم اللغة العربيةفيستخدم حتى الآن فيالتعليم الرسمي (الـمدارسالعامة والـمدارس الدينية) ويستمر تكميله، سواء من حيث الـمناهج أو أهداف التعليم أو الـمواد أو الطريقة أو استراتيجيات التعليم،وكذلك الوسائل الـمستخدمة.تعليم اللغة العربية تحتاج إلي تطوير المنهج الجديد الذي يتركز فى تعليم الكفاءات وهي الكفاءات النوعية والخاصة و الكفاءات اللغوية والكفاءات التواصلية.هذه الكفاات مرتبطة بعضها من بعض ولاسيما فى الكفاات اللغوية والتواصلية. الكلمات المفاتحية : المنهج الدراسي، تعليم اللغة العربية، المعهد (باسانترين)، الكفاية